Polymer Materials in Sensors, Actuators and Energy Conversion - Wang, Jung-Chang (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Polymer-based materials applications in sensors, actuators, and energy conversion play a key role in recently developing areas of smart materials and electronic devices. These areas cover the synthesis, structures, and properties of polymers and composites, including energy-harvesting devices and energy-storage devices for electromechanical (electrical to mechanical energy conversion) and magneto-mechanical (magnetic to mechanical energy conversion), light-emitting devices, and electrically driving sensors. Therefore, the modulation of polymer-based materials and devices for controlling the detection, actuation, and energy with functionalized relative device can be achieved with the present reprint, comprising 12 chapters.This reprint is principally concerned with the topic of materials of materials, especially polymers. The contents not only involve essential information but also possess many novel academic applications in the fields. This Special Issue's title is "Polymer Materials in Sensors, Actuators and Energy Conversion" and covers the research field of polymers .Finally, I am very proud of my dear wife Winnie, son Vincent, and daughter Ruby. I thank them for supporting me in finishing the reprint. The reprint, involving 2 reviews and 10 regular papers, has been accomplished, and I am deeply thankful to all the authors for their assistance in producing a reprint with considerable number of chapters. I also hope that readers can achieve some useful understanding of polymer materials in sensors, actuators, and energy conversion, and that that they will be employed by scientists and researchers.